2022
DOI: 10.15252/embr.202154275
|View full text |Cite
|
Sign up to set email alerts
|

Transforming primary human hepatocytes into hepatocellular carcinoma with genetically defined factors

Abstract: Our understanding of human hepatocellular carcinoma (HCC) development and progression has been hampered by the lack of in vivo models. We performed a genetic screen of 10 oncogenes and genetic mutations in Fah‐ablated immunodeficient mice in which primary human hepatocytes (PHHs) are used to reconstitute a functional human liver. We identified that MYC, TP53R249S, and KRASG12D are highly expressed in induced HCC (iHCC) samples. The overexpression of MYC and TP53R249S transform PHHs into iHCC in situ, though th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 76 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…It has been reported that FAP was expressed in the stroma of human colorectal tumors and other epithelial malignancies, and it was almost undetected in most normal tissues (Garin‐Chesa et al, 1990). It has been reported that FAP was expressed in induced HCC but not in normal livers (Jiang et al, 2022), and FAP was highly expressed in advance‐staged HCC tumors compared to early lesions (Zou et al, 2018). The colon tumors patients with high FAP expression were correlated with a high risk of metastasis and recurrence (Henry et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that FAP was expressed in the stroma of human colorectal tumors and other epithelial malignancies, and it was almost undetected in most normal tissues (Garin‐Chesa et al, 1990). It has been reported that FAP was expressed in induced HCC but not in normal livers (Jiang et al, 2022), and FAP was highly expressed in advance‐staged HCC tumors compared to early lesions (Zou et al, 2018). The colon tumors patients with high FAP expression were correlated with a high risk of metastasis and recurrence (Henry et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that FAP was expressed in induced HCC but not in normal livers (Jiang et al, 2022), and FAP was highly expressed in advance-staged HCC tumors compared to early lesions ( Zou et al, 2018). The colon tumors patients with high FAP expression were correlated with a high risk of metastasis and recurrence (Henry et al, 2007).…”
Section: Fap Overexpression In Cafs Promoted Proliferation and Migrat...mentioning
confidence: 99%
“…MUC1 served as an efficient CAR-T targets and was proved important in breast cancer treatment, so the single resistance to targeted glycosylation (MUC1) is designed to be a kind of CAR-T cell, in xenotransplantation model shows targeted cell toxicity. In vitro studies also have shown that MUC1 has specific cytotoxicity to HCC cell lines, which may be applied to clinical CAR-T therapy for HCC [15].…”
Section: Breakthroughs Of Car-t Therapy In Solid Tumormentioning
confidence: 99%
“…3). For example, CAR-T cells targeting AFP, EGFRvIII, B7H3, EpCAM, MUC1, NKG2DL, PD-L1, and CD147 were demonstrated in preclinical studies [189,[284][285][286][287][288][289]. Many clinical trials for these targets have also been registered and conducted.…”
Section: Liver Cancermentioning
confidence: 99%